KEARIFAN SUFISME DALAM ISLAMISASI JAWA - Purwadi, Purwadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Purwokerto, 2011)
This article shows the wisdom of Sufism on social transformationin Java at the early spread of Islam. Sufism approach tends to emphasizeon self-awareness while accommodating ornamental outer symbols. Thispattern makes the process of being Muslims in Java more peaceful andacceptable for those who already have certain believe and religion (animism,Hinduism and Buddhism).